Exploring the interplay of MTHFR and FGG polymorphisms with serum levels of adiponectin and leptin in pediatric lupus nephritis: a pilot study (2024)
Background Adiponectin and leptin are pivotal in the regulation of metabolism. Pediatric lupus nephritis (pLN), a manifestation of childhood systemic lupus erythematosus (SLE) affecting the kidneys, is associated with impaired adipokine levels, suggesting a role in pLN pathogenesis. The aim of this study was to explore the potential relationship between specific single-nucleotide polymorphisms (SNPs)—methylenetetrahydrofolate reductase (MTHFR) rs1801131 and fibrinogen gamma chain (FGG) rs2066865—and the serum levels of leptin and adiponectin in patients with pLN. Methods Ninety-eight pLN patients and one hundred controls were enrolled in the study. Serum leptin and adiponectin levels were measured using ELISA. DNA extraction and real-time PCR genotyping were performed for MTHFR rs1801131 and FGG rs2066865 SNPs. Results Compared to healthy controls, pLN patients exhibited significantly greater serum leptin (11.3 vs. 18.2 ng/ mL, p < 0.001) and adiponectin (18.2 vs. 2.7 ug/mL, p < 0.001). Adiponectin levels were positively correlated with proteinuria (p < 0.05), while leptin levels positively correlated with proteinuria, SLE disease activity index-2000 (SLEDAI-2K), and cyclophosphamide usage (all p < 0.05). There was no significant association between MTHFR rs1801131 or FGG rs2066865 SNPs and pLN in either codominant or allelic models (all p > 0.05). However, the AG genotype of FGG gene rs2066865 SNP was significantly associated with high leptin levels (> 15 ng/mL) (p = 0.01). Conclusion Serum adiponectin and leptin levels are associated with pathological manifestations of pLN. High leptin levels are associated with the AG genotype of FGG rs2066865 SNP in pLN patients, suggesting direct involvement in disease progression and potential utility as a disease biomarker.